The Influence of Workload and Job Stress Against Burnout and Its Impact on Employee Performance of PT Bank BPD Bali Main Branch Denpasar - Ni Nyoman Rini Florenta (JUSTBEST: Journal of Sustainable Business and Management, 2022)
The factor that can influence the level of success of the bank itself is employee performance. Good performance is the optimal performance that follows procedures or procedures in accordance with established standards. This study aims to determine and explain the effect of workload and work stress on burnout and its impact on employee performance with research subjects of all employees at the Bali BPD Main Branch Denpasar office. The research design used to address this problem is quantitative with a population and sample of 67 people. The data used in this study are primary and secondary data both quantitative and qualitative data. Data analysis using the Partial Least Square (PLS) method with the results of the study showed that workload was not significantly positive effect on work stress, workload was not significantly negative effect on burnout, job stress was not significantly positive effect on burnout, workload had a positive and significant effect on employee performance, job stress has no significant negative effect on employee performance, burnout has no significant negative effect on employee performance at PT Bank BPD Bali Main Branch Denpasar. It is recommended to further researchers to examine other branch offices as a comparison and examine other variables that affect Employee Performance such as work motivation, leadership style, organizational culture, compensation or job satisfaction.